Estudios de investigación sobre hipertrofia adenoidea y alteraciones craneofaciales. Scoping Review (2022)
Objective: to carry out a narrative review of the state of publication on the means of diagnosis of adenoid hypertrophy and its relationship with craniofacial and maxillary alterations, during the period from 2010 to 2021. Materials and Methods: A bibliographic search was carried out in the Databases Pubmed, Science Direct and Web of Science. The RAYYAN program was used for the selection of the articles, experimental articles, retrospective studies, randomized clinical trials were included. Gómez's methodology was followed to carry out this scoping review. Results: the ideal means of diagnosis for adenoid hypertrophy was lateral skull radiography, the most used method was the method of Fujioka et al., 1973, the craniofacial alterations generated by adenoid hypertrophy are convex profile, hyperdivergent facial pattern, mandibular plane highly downward and posteriorly inclined, reduced posterior facial height, deep and compressed palate and palatal inclined maxillary incisors and proclined mandibular incisors Conclusions: Evidence supports that oral breathing caused by adenoid hypertrophy produces changes in the development of children, generating craniofacial and dental alterations such as class II and class III relationships, open bites combined with mandibular prognathism